Effects of strontium ranelate on bone formation in the mid-palatal suture after rapid maxillary expansion - Zhao SY; Wang XX; Li N; Chen Y; Su YR; Zhang J (Dove Medical Press, 2015)
Shuya Zhao,1,* Xuxia Wang,2,* Na Li,3 Yun Chen,1 Yuran Su,1 Jun Zhang1 1Department of Orthodontics, 2Department of Oral and Maxillofacial Surgery, Faculty of Stomatology, Shandong University; 3Department of Orthodontics, Shandong Provincial Qianfoshan Hospital, Jinan, People’s Republic of China *These authors contributed equally to this work Background: The aim of this experimental study was to investigate the effects of strontium ranelate on bone regeneration in the mid-palatal suture in response to rapid maxillary expansion (RME).Methods: Thirty-six male 6-week-old Wistar rats were randomly divided into three groups, ie, an expansion only (EO) group, an expansion plus strontium ranelate (SE) group, and a control group. An orthodontic appliance was set between the right and left upper molars of rats with an initial expansive force of 0.98 N. Rats in the SE group were administered strontium ranelate (600 mg/kg body weight) and then euthanized in batches on days 4, 7, and 10. Morphological changes in the mid-palatal suture were investigated using micro-computed tomography and hematoxylin and eosin staining after RME. Bone morphogenetic protein-2 expression in the suture was also examined to evaluate bone formation in the mid-palatal suture. Image-Pro Plus software was then used to determine the mean optical density of the immunohistochemical images. Analysis of variance was used for statistical evaluation at the P<0.05 level.Results: With expansive force, the mid-palatal suture was expanded, but there was no statistically significant difference (P>0.05) between the SE and EO groups. The bone volume of the suture decreased after RME, but was higher in the SE group than in the EO group on days 7 and 10. Further, expression of bone morphogenetic protein-2 in the SE group was higher than in the other two groups (P<0.05).Conclusion: Strontium ranelate may hasten new bone formation in the expanded mid-palatal suture, which may be therapeutically beneficial in prevention of relapse and shortening the retention period after RME. Keywords: strontium ranelate, rapid maxillary expansion, micro-computed tomography, bone morphogenetic protein-2, bone formation